Corporate governance and innovation performance: a contingency perspective - Wu, Shuqin (2019)
This study advances the study of the corporate governance and innovation performance by considering the effect of institutional environment-the existence of the state. The aim of this dissertation is to identify the role of the state in examining the effectiveness of corporate governance on innovation performance. Specifically, this study discusses the impact of corporate governance on innovation performance in the context of the specific institutional environment that whether enterprises are SOEs or not. Corporate governance in terms of managerial ownership, ownership concentration, foreign ownership and absorptive capacity is discussed separately. Using panel data from 152 companies with qualifications, the effectiveness of corporate governance on innovation performance is separately tested in the full sample and two subsamples: SOEs and Non-SOEs. This study finds that managerial ownership has a positive effect on innovation performance only in SOEs. Ownership concentration harms innovation performance in both SOEs and non-SOEs. However, what is worth noting is that foreign ownership does not affect innovation performance in this study. Besides, absorptive capacity positively shapes innovation performance in the full sample and two subsamples. These findings help researchers better understand how corporate governance mechanism affects innovation performance under different contexts-SOEs and non-SOEs. Finally, this study discusses the implications and provides direction for future research.